Estimated change in prevalence of abnormal thyroid-stimulating hormone levels in China according to the application of the kit-recommended or NACB standard reference interval - Yongze Li, Ph.D. (EClinicalMedicine, 2021)
Background: Both the kit-recommended and United States National Academy of Clinical Biochemistry (NACB) standard thyroid-stimulating hormone (TSH) reference intervals (RIs) are used to determine thyroid dysfunction in clinical practice and epidemiological surveys in China. However, a number of kit-recommended RIs were derived from the European or United States reference population. Methods: A nationally representative cross-sectional study with 78,470 enrolled participants aged 18 years or older from China was performed. Serum concentrations of thyroid hormones, TSH, thyroid antibodies (by Roche Diagnostics), and urine iodine concentration (UIC) were measured. Findings: The abnormal TSH weighted prevalence was 15.33% (95% CI, 14.24% to 16.49%) according to the kit-recommended RI and 6.89% (6.46% to 7.34%) according to the NACB standard RI. The NACB standard prevalence of abnormal TSH was associated with an absolute change in abnormal TSH prevalence of −11.20% (−12.23% to −10.18%) among women. When estimating the proportion of supranormal TSH levels according to background characteristics, the NACB standard definition decreased the prevalence by more than 10% in some categories, with the highest absolute difference of −13.92% (−15.52% to −12.33%) observed among the elderly, −12.85% (−13.68% to −12.02%) among those with UIC ≥300 μg/L, and −12.15% (−13.02% to −11.28%) among non-smokers. For subnormal TSH, with the highest absolute difference of 3.17% (2.74% to 3.61%) observed among regular smokers, 3.11% (2.49% to 3.74%) among the elderly, and 2.53% (2.29% to 2.77%) among those with BMI <25. Interpretation: For adults in China, the NACB standard RI of TSH reveals a lower estimated prevalence of supranormal TSH levels than the kit-recommended RI. Because of the public health significance of overt and subclinical hypothyroidism and the very large population base in China, the TSH RI should be further assessed. Funding: National Health Commission of the People's Republic of China and National Natural Science Foundation of China.